Curtailing Male Rape in Nigeria: Legal Issues and Challenges - Aidonojie, Paul Atagamen; Antai, Godswill Owoche; John, Damina Joshua; Ibeh, Success; Adebayo, Adesoji Kolawole (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2024)
Despite the increasing prevalence and significant impact of male rape on the lives of many men in Nigeria, the issue has received limited attention. This study employs a hybrid research methodology to investigate the occurrences of male rape and the challenges in addressing its incidence in Nigeria. A total of 303 questionnaires were distributed to respondents, and the data were analyzed using descriptive and analytical methods. The findings reveal that male rape is indeed a widespread issue in Nigeria, and the existing legal framework is insufficient to effectively address this problem. Additionally, the study highlights that various legal, social, and psychological factors hinder efforts to reduce male rape in the country. The study concludes by emphasizing that rape is not a crime that exclusively affects women, but also constitutes a violent act against men. Therefore, the Nigerian government and stakeholders within the criminal justice system must take urgent steps, through legal reforms and justice mechanisms, to combat the silent but growing crisis of male rape in Nigerian society.